The Development of Virtual Textile Chemistry Laboratory in Learning Making Cellulose-Based Regeneration Fibers Based on Learning Paradigms in the Industrial Revolution 4.0 Era - Wiana, Winwin (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to design and create a virtual chemical textile laboratory model as an effort to improve students' understanding of learning Textile Chemistry, especially on the subject of making cellulose-based regenerative textile fibers that have a high level of abstraction and complexity. Theoretical learning in the form of verbal symbols, empirically is not representative enough to explain the concept of the system that is needed, so that the possibility is not affordable (likely to inaccessible) by students which effected to the lessen of learning experiences. These conditions have implications for the lack of student understanding of these processes which is indicated by the acquisition of low learning outcomes. The specific target of this research is to produce a virtual laboratory device as a simulation medium for learning textile chemistry on the subject of making effective cellulose-based regenerative fibers. Furthermore, the model developed is validated to get input from experts related to the technology used, design and process content in the developed model. The validation results show that this model is suitable for use in the study of textile chemistry and can be used to improve students' understanding of the material for making cellulose-based regenerative textile fibers. In the limited trials that have been carried out, there are some features, image choices, and some simulations that need to be refined to avoid students' misinterpretations of the planned chemical process concept. Students involved in the trials are more motivated to continue learning related concepts that have been learned. In subsequent studies this model will be tested on a broader scale to measure its effect on the mastery of concepts and its ability to improve learning outcomes in textile chemistry courses, on the material for making cellulose-based regenerative fibers.